2022
DOI: 10.1111/ajd.13895
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab treatment demonstrated high drug survival and sustained effectiveness in patients with severe chronic plaque psoriasis: 21‐month analysis in Australian routine clinical practice (SUSTAIN study)

Abstract: Background Drug survival measures the rate and duration of adherence to a given therapeutic agent and evaluates its long‐term effectiveness, safety, and real‐world utility. The SUSTAIN study sought to establish the drug survival and effectiveness of secukinumab for patients with severe chronic plaque psoriasis (CPP) in the Australian clinical setting. Methods Data of all patients (aged ≥18 years) from Australasian Psoriasis Registry (APR) treated with secukinumab were analysed. The primary objective was to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…The same is corroborated by other real-world studies, wherein higher proportion of biologic-naïve patients achieved PASI 75/90/100 responses than biologic-experienced patients. 9 , 31 The current study also demonstrated the same trend for PASI 75 and 90; however, the higher proportion of biologic-experienced patients achieved PASI 100 than biologic-naïve patients. Interestingly, a stark difference in the proportion of patients achieving PASI 100 in the biologic-naïve cohort versus biologic-experienced cohort was observed in another study from Japan.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The same is corroborated by other real-world studies, wherein higher proportion of biologic-naïve patients achieved PASI 75/90/100 responses than biologic-experienced patients. 9 , 31 The current study also demonstrated the same trend for PASI 75 and 90; however, the higher proportion of biologic-experienced patients achieved PASI 100 than biologic-naïve patients. Interestingly, a stark difference in the proportion of patients achieving PASI 100 in the biologic-naïve cohort versus biologic-experienced cohort was observed in another study from Japan.…”
Section: Discussionsupporting
confidence: 75%
“… 32 , 33 Other studies assessing the effectiveness of secukinumab on patients with psoriasis also had higher percentage of patients exposed to biologics at baseline. 9 , 34 , 35 These studies indicated much higher accessibility of biologics by the Western population compared to the Korean population.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations